2016
DOI: 10.1080/09638288.2016.1224276
|View full text |Cite
|
Sign up to set email alerts
|

Workplace accommodations for persons with physical disabilities: evidence synthesis of the peer-reviewed literature

Abstract: This evidence synthesis provides an overview of the peer-reviewed literature of value to occupational rehabilitation professionals and employers seeking guidance on workplace accommodation policies and practices for persons with physical disabilities. A wide range of accommodation options is available for addressing physical, social, and attitudinal barriers to successful employment. Besides physical/technological modifications, accommodations to enhance workplace flexibility and worker autonomy and strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 93 publications
4
64
1
3
Order By: Relevance
“…An alternative explanation might be lay misconceptions about the nature of persons with a psychological disability, with employers assuming that persons with psychological disabilities would require greater supervision and attention (Ju, Roberts & Zhang 2013). However, Padkapayeva et al (2016) pointed out another view concerning the cost of adapting work tasks, work pace and working hours; namely that these forms of adaptations could require an ongoing effort from the employer, which might affect their willingness to adapt the workplace and hire persons with psychological disabilities. The results also showed that persons with a communicative disability differed from the other groups in a number of dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation might be lay misconceptions about the nature of persons with a psychological disability, with employers assuming that persons with psychological disabilities would require greater supervision and attention (Ju, Roberts & Zhang 2013). However, Padkapayeva et al (2016) pointed out another view concerning the cost of adapting work tasks, work pace and working hours; namely that these forms of adaptations could require an ongoing effort from the employer, which might affect their willingness to adapt the workplace and hire persons with psychological disabilities. The results also showed that persons with a communicative disability differed from the other groups in a number of dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, workplace adaptations may involve limited costs and are beneficial both to employers and PwDs (Hartnett, Stuart, Thurman, Loy, & Batiste, 2011;Nevala et al, 2015;Schartz, Hendricks, & Blanck, 2006;Schur et al, 2014). In particular, providing workplace flexibility by modifying job tasks, work scheduling and/or location appears not to be costly, though it does require on-going effort (Padkapayeva et al, 2016). Public financial support is available to cover a part of adaptation costs for employers (Hvinden, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Workplace supports represent an important employer‐led strategy to address the challenges that can impact sustained and productive employment 12 . Aligning with previous research, participants in our study required diverse workplace supports to encourage labor market engagement including prescription drug coverage, scheduling flexibility, extended health benefits, modified job duties, and opportunities to informally modify work 8‐11 . Interestingly, the types of workplace support that were most needed were similar for those with and without disabilities.…”
Section: Discussionmentioning
confidence: 53%
“…Workplace supports modify aspects of the work context that can contribute to employment limitations 6 . Studies indicate that the most‐needed workplace supports reported by people with disabilities include health benefits (e.g., prescription drug coverage), work modification (e.g., scheduling flexibility), and job accommodation (e.g., accessible workstations) 6‐11 . People with disabilities also indicate that workplace support needs are often unmet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation